Corn vs. sorghum, pellets vs. meal, and soybean oil meal vs. a mixed protein for growing-finishing pigs - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
One hundred forty feeder pigs weighing approximately 60 to 80 pounds each and averaging 12 weeks of age were randomly divided by weight into groups of 14 pigs each. The pigs had been vaccinated previously for hog cholera and had been wormed with piperuzine. All pigs had been on concrete from birth and they had been raised under complete confinement. Each group of 14 pigs was placed in a pen 7 feet wide by 28 feet long with 16 feet of the pen under roof. Complete rations, either meal or pellets, were self-fed. An all-steel three-hole self-feeder was used in each pen. Water was always available from automatic waterers.
Keywords: Swine; Corn vs. sorghum; Pellets vs. Meal; Soybean oil meal vs. mixed protein; Growing-finishing pigs